Features and significance of the qualification of criminal offenses of illegal cutting of trees and shrubs, as well as destruction and damage to forests - Aitimov, B.Zh.; Yernishev, K.А. (Bulletin of the Karaganda University “Law Series”, 2024)
The purpose of the research is to analyze the theory of prosecution for illegal cutting of trees and bushes, de-struction, damage to forests in accordance with Articles 340, 341 of the Criminal Code of the Republic of Kazakhstan and focus on its practice, consider the main issues of prosecution for these criminal offenses, identify the main barriers to prosecution and give the necessary legislative proposals for its implementation improvement. The Article discusses the importance of preventing illegal cutting of trees and shrubs, destruc-tion, and damage to forests, as well as considering criminal liability for these acts. At the same time, having dwelled on the current state of qualification of these criminal offenses, points were identified that should be considered during the investigation and judicial review of these criminal offenses, and relevant legislative proposals were considered. The relevant norms of the Forest Code of the Republic of Kazakhstan, containing requirements related to the protection of trees and shrubs, as well as the features of bringing to criminal liabil-ity for illegal cutting of trees and bushes, destruction, damage to forests, provided for in Articles 340, 341 of the Criminal Code of the Republic of Kazakhstan, are analyzed. A comparative legal analysis of the legisla-tion of the countries of Germany and Hungary was also carried out to determine the European practice of rec-ognizing “forests” as a unique natural resource. In addition, an analysis of judicial practice on criminal of-fenses related to illegal cutting of trees and bushes, as well as destruction and damage to forests, and the regu-latory ruling of the Supreme Court related to the application of Articles 340, 341 of the Criminal Code of the Republic of Kazakhstan was carried out.